Oral mucosal lesions in a representative cross-sectional study of aging Germans - Reichart, PA (Blackwell Synergy, 2000)
To determine prevalence of oral mucosal lesions in a crosssectional study among aging Germans. Methods: Three specially trained dental teams examined adults (35–44 yrs, Group 1) and senior individuals (65–74 yrs, Group 2) in 90 sample points of which 60 were located in the former West and 30 in the former East part of Germany. The spectrum comprised 28 different oral lesions with subforms. Results: 655 individuals in Group 1 (35–44 yrs) and 1367 individuals in Group 2 (65–74 yrs) were studied.